Financially Motivated LMP Manipulation By Aggregators in Power Markets - (:unkn) unknown (My University, 2019)
Renewable energy accounts for a sizeable share within modern power systems and aggregators of renewable generators play an important role in the electricity market. However, because renewable generators produce power intermittently, it is hard to monitor and supervise the behavior of the aggregators. There is a chance for aggregators to manipulate the locational marginal prices (LMPs) in the power market by curtailing generation in order to increase their profits. In this thesis we propose a tri-level model that can quantify aggregators’ potential profits. This model is based on both a real-time optimal dispatch and an LMP clearing procedure. With this model, the relationship between curtailment of generation and profits of aggregators was studied by using different backup generators in an IEEE 14-bus power system. At the same time, we found the most profitable point at which aggregators curtail generation. We also used the same IEEE 14-bus power system to devise a resilience strategy to keep LMPs steady throughout the whole power system. This resilience strategy led to a decline in aggregators’ motivation to manipulate LMPs in power markets. In the study, we show that the aggregators can increase their profits through the curtailment of generation and this behavior can lead to significant LMP changes in the whole power system. The profit of aggregators can be different when the independent system operators (ISOs) use different generators to make up the financially motivated curtailment. Further, this thesis shows that aggregators have the potential to conduct financially motivated LMP manipulation in the power market and it can push ISOs to improve the related management rules.